Increase of enzyme activity through specific covalent modification with fragments. Issue 11 (4th October 2017) - Darby, John F.; Atobe, Masakazu; Firth, James D.; Bond, Paul; Davies, Gideon J.; O'Brien, Peter; Hubbard, Roderick E.
Abstract : Structure-guided tethering of a fragment activator significantly increases enzyme activity. Abstract : Modulation of enzyme activity is a powerful means of probing cellular function and can be exploited for diverse applications. Here, we explore a method of enzyme activation where covalent tethering of a small molecule to an enzyme can increase catalytic activity ( k cat / K M ) up to 35-fold. Using a bacterial glycoside hydrolase, BtGH84, we demonstrate how small molecule "fragments", identified as activators in free solution, can be covalently tethered to the protein using Michael-addition chemistry. We show how tethering generates a constitutively-activated enzyme-fragment conjugate, which displays both improved catalytic efficiency and increased susceptibility to certain inhibitor classes. Structure guided modifications of the tethered fragment demonstrate how specific interactions between the fragment and the enzyme influence the extent of activation. This work suggests that a similar approach may be used to modulate the activity of enzymes such as to improve catalytic efficiency or increase inhibitor susceptibility.